The last house on Needless Street - Ward, Catriona (Nightfire, 2021)
"Catriona Ward's The Last House on Needless Street is a shocking and immersive read perfect for fans of Gone Girl and The Haunting of Hill House. "The new face of literary dark fiction." -Sarah Pinborough, New York Times bestselling author of Behind Her Eyes. "The buzz...is real. I've read it and was blown away. It's a true nerve-shredder that keeps its mind-blowing secrets to the very end." -Stephen King. In a boarded-up house on a dead-end street at the edge of the wild Washington woods lives a family of three. A teenage girl who isn't allowed outside, not after last time. A man who drinks alone in front of his TV, trying to ignore the gaps in his memory. And a house cat who loves napping and reading the Bible. An unspeakable secret binds them together, but when a new neighbor moves in next door, what is buried out among the birch trees may come back to haunt them all"--